2018
DOI: 10.1080/09546634.2018.1484873
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab/IVIG in pemphigus – a 10-year study with a long follow-up

Abstract: Rituximab is an effective and safe treatment for pemphigus and should be considered earlier in the algorithm of pemphigus treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Initial IVIG therapy rapidly elevates total circulating Ig levels, which is thought to stimulate homeostatic antibody-catabolic mechanisms, leading to lowering of serum levels of IgG1 and IgG4 anti-Dsg 1 and Dsg 3 antibodies (Green and Bystryn, 2008) while normal antibodies are replaced by those in subsequent IVIG doses: this is a particularly useful treatment when fast onset of therapy and lower risk of infection is needed. Combining rituximab and IVIG can be effective for the treatment of refractory pemphigus cases and may even induce long-term complete remission with lower risk of infection (Hamadah et al, 2019): accordingly, a clinical trial was started in June 2020 to evaluate the efficacy and safety of early use of rituximab with or without IVIGs in patients with moderate to severe pemphigus (NCT04400994). Immunoadsorption, which also rapidly removes anti-Dsg IgG from the circulation, has also been trialled in conjunction with conventional immunosuppressive treatment and intravenous rituximab (Eming and Hertl, 2006;Behzad et al, 2012).…”
Section: Adjunct Therapiesmentioning
confidence: 99%
“…Initial IVIG therapy rapidly elevates total circulating Ig levels, which is thought to stimulate homeostatic antibody-catabolic mechanisms, leading to lowering of serum levels of IgG1 and IgG4 anti-Dsg 1 and Dsg 3 antibodies (Green and Bystryn, 2008) while normal antibodies are replaced by those in subsequent IVIG doses: this is a particularly useful treatment when fast onset of therapy and lower risk of infection is needed. Combining rituximab and IVIG can be effective for the treatment of refractory pemphigus cases and may even induce long-term complete remission with lower risk of infection (Hamadah et al, 2019): accordingly, a clinical trial was started in June 2020 to evaluate the efficacy and safety of early use of rituximab with or without IVIGs in patients with moderate to severe pemphigus (NCT04400994). Immunoadsorption, which also rapidly removes anti-Dsg IgG from the circulation, has also been trialled in conjunction with conventional immunosuppressive treatment and intravenous rituximab (Eming and Hertl, 2006;Behzad et al, 2012).…”
Section: Adjunct Therapiesmentioning
confidence: 99%
“…With the clinical success and subsequent United States Food and Drug Administration's approval of rituximab for pemphigus, reviewed in detail elsewhere, much attention has been given towards optimizing B‐cell targeting . Although small studies suggest rituximab may not be as effective for BP as for pemphigus, at this time rituximab is one of the most effective treatments for EBA .…”
Section: Evolving Therapeutic Targetsmentioning
confidence: 99%
“…The application of rituximab and intravenous immunoglobulin (IVIg) in combination has shown how different aspects of these diseases can be effectively targeted . While these therapies have become more accepted as a standard of care, corticosteroids are still generally required for prolonged periods of time for acute disease . Likewise, relapses are common, especially in shorter treatment protocols, rather than protracted protocols .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is no consensus on the dose regimen and duration for PV. A previous report suggested various successful rituximabregimens for pemphigus such as rheumatology, oncology, and IVIG combination protocols [4]. Other reports demonstrated that lowdose rituximab (375 mg/m 2 , 2 times, 1-2 weeks apart) had similar effects in autoimmune diseasescompared to high-dose rituximab (1000mg, 2 times, 2 weeks apart) in the time to achieve rapid improvement [5][6][7].…”
mentioning
confidence: 99%